Employment Opportunities and High School Completion during the COVID-19 Recession - Kunwon Ahn; Jun Yeong Lee; John V. Winters (Institute of Labor Economics (IZA), 2020)
COVID-19 created major disruptions for young people including health concerns, school closures, reduced social opportunities, and a wilting economy. We examine the effect of COVID-19 on high school completion in the United States. We find that high school completion rates increased considerably in 2020 compared to previous years. We investigate various mechanisms and find that worse employment conditions were the driving force. The lower opportunity costs of schooling because of the pandemic recession encouraged more young people to complete high school. The pandemic created extensive problems in education, but fortunately it did not reduce overall high school completion rates.
Keywords: I2; J24; 330; education; employment; recession; COVID-19; human capital